Association between coronavirus disease 2019 and new-onset autoimmune diseases during the early phase of the pandemic - Joung Ha Park; Min-Taek Lee; Sun-Young Jung; Sang Tae Choi; Seong-Ho Choi (PLoS ONE, 2026)
Emerging evidence suggests that viral infections, including SARS-CoV-2, may trigger autoimmunity. This study investigated the risk of developing autoimmune diseases following coronavirus disease 2019 (COVID-19) using sequence symmetry analysis. We utilized nationwide population-based data from South Korea by linking the National Health Insurance Service database with the Korea Centers for Disease Control and Prevention Agency COVID-19 registry. This study included 2,678 patients with COVID-19 and 92,725 patients without COVID-19 identified between 01/10/2020 and 30/06/2021, during the early phase of the pandemic. Both groups consisted of individuals who were diagnosed with autoimmune diseases within 180 days before or after the index date. We calculated the adjusted sequence ratio (aSR) to compare the incidence of autoimmune diseases within 180 days before and from 14 to 180 days after the index date (the COVID-19 diagnosis date for the COVID-19 group and the first medical visit for the non-COVID-19 group). The differences in autoimmune disease incidence between the groups were evaluated using the ratio of aSR (RaSR). The incidence of newly diagnosed autoimmune diseases—Behcet’s disease (RaSR, 2.03), ankylosing spondylitis (2.04), ulcerative colitis (1.15), Crohn’s disease (2.22), psoriasis (1.27), type 1 diabetes mellitus (1.61), and Graves’ disease (1.14)—was significantly higher in the COVID-19 group than in the non-COVID-19 group after the index date. Subgroup analysis comparing patients with non-severe COVID-19 with those without COVID-19 yielded consistent findings. Furthermore, the incidence of inflammatory bowel diseases was higher in the non-severe COVID-19 group after the index date (RaSR, 1.29). These findings reinforce growing evidence that COVID-19 could induce autoimmunity and increase the risk of developing autoimmune diseases. Therefore, clinicians should remain vigilant for potential autoimmune complications in patients with a history of COVID-19 when clinically indicated.